1991
DOI: 10.3168/jds.s0022-0302(91)78330-6
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Ruminal Infusion of Sodium Bicarbonate. 1. Influence of Postfeeding Infusion Interval on Ruminal Milieu

Abstract: Four ruminally cannulated, lactating Holstein cows were assigned to a 4 x 4 Latin square to monitor the effects of intraruminal NaHCO3 infusion on changes in the rumen environment. Sodium bicarbonate (110 g), dissolved in 3.8 L of water, was infused twice daily at a constant rate for 2 h starting at 0, 2, or 4 h postfeeding. All cows had access to their diet containing sorghum silage and concentrate in a 35:65 ration (DM basis) for 45 min twice daily. Ruminal fluid was collected at feeding and every 30 min pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
3

Year Published

1991
1991
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
9
3
Order By: Relevance
“…The 4-6Bic infusion resulted in a higher [H+] than for Ctrl at 0 and 2 h, but ~educed [H+] after NaHco 3 infusion began (5.5 h) and again at 7.5 h postfeeding. Hogue et al (1991) also reported that the effects of intra-ruminal infusion of NaHco 3 on [H+] were most dramatic during the infusion interval. As compared to Ctrl, mean rumina!…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The 4-6Bic infusion resulted in a higher [H+] than for Ctrl at 0 and 2 h, but ~educed [H+] after NaHco 3 infusion began (5.5 h) and again at 7.5 h postfeeding. Hogue et al (1991) also reported that the effects of intra-ruminal infusion of NaHco 3 on [H+] were most dramatic during the infusion interval. As compared to Ctrl, mean rumina!…”
Section: Resultsmentioning
confidence: 94%
“…An increase in ruminal turnover time was observed for 0 to 2 and 4 to 6 h postfeeding intraruminal infusion of sodium bicarbonate (Hogue et al, 1991). The acid-base status of an animal is associated with environmental temperature;…”
Section: Decreased Rumen Ph Results In Depression Of Molarmentioning
confidence: 97%
See 3 more Smart Citations